Estimation of third order elastic constants of piezoceramics using DC biased impedance measurements - Claes, Leander; Hölscher, Jonas; Friesen, Olga; Scheidemann, Claus; Hemsel, Tobias; Henning, Bernd (2025 International Congress on Ultrasonics)

Modeling and simulation of the behavior of piezoceramics with the discontinuous Galerkin method - Spieker, Carsten; Förstner, Jens; Hölscher, Jonas; Claes, Leander; Henning, Bernd (2025 International Congress on Ultrasonics)

Multiscale thermo-piezoelectric simulations using the finite element method - Hölscher, Jonas; Friesen, Olga; Claes, Leander; Spieker, Carsten; Förstner, Jens; Henning, Bernd (2025 International Congress on Ultrasonics)

Entwicklung und Evaluation des Konzepts Datenbewusstsein für informatische Bildung - Höper, Lukas
Heutzutage sind datengetriebene digitale Artefakte aus unserem Alltag nicht mehr wegzudenken. Bei der Interaktion mit datengetriebenen Artefakten spielen Daten eine zentrale Rolle, unter anderem persönliche Daten von Schüler:innen, die solche Systeme nutzen. Aus der Perspektive informatischer Bildung besteht ein wichtiges Ziel darin, Schüler:innen zu befähigen, datengetriebene digitale Artefakte aus ihrem Alltag zu verstehen, denen gegenüber informierte und reflektierte Positionen einzunehmen und die digitale Welt aktiv mitzugestalten. Das setzt etwa voraus, dass Schüler:innen das Gelernte aus dem Informatikunterricht in ihren alltäglichen Interaktionen mit datengetriebenen digitalen Artefakten anwenden können, um sich mit diesen Artefakten und der Rolle von Daten auseinanderzusetzen und darauf aufbauend selbstbestimmt, mündig und verantwortungsvoll zu handeln. Für diese Ziele informatischer Bildung wird in dieser Arbeit das fachdidaktische Konzept Datenbewusstsein entwickelt und evaluiert. Datenbewusstsein stellt Schüler:innen ein sogenanntes Erklärmodell als Zugang zur datengetriebenen Welt bereit und zielt darauf ab, dass sie damit ihre eigene Rolle in Interaktionen mit datengetriebenen digitales Artefakten sowie die Rolle von Daten darin wahrnehmen, verstehen und reflektieren können. Dadurch soll Datenbewusstsein zu einer selbstbestimmten, mündigen und verantwortungsvollen Handlungsfähigkeit in einer datengetriebenen Welt beitragen. Die Entwicklung und Evaluation des Konzepts orientiert sich am Design-Based Research Ansatz, wofür aus informatikdidaktischer Perspektive ein eigenes Vorgehensmodell entwickelt wurde. Das Forschungsvorhaben hat zwei übergeordnete Ziele: Erstens soll eine theoretische Konzeption von Datenbewusstsein für informatische Bildung und zweitens ein didaktischer Ansatz zur Förderung von Datenbewusstsein entwickelt werden. In drei Zyklen wird die Förderung von Datenbewusstsein im Informatikunterricht mithilfe von Unterrichtsinterventionen empirisch untersucht. Schwerpunkte liegen dabei unter anderem auf dem Verständnis der Schüler:innen von der Rolle von Daten in datengetriebenen digitalen Artefakten, der Förderung ihrer Auseinandersetzung mit solchen digitalen Artefakten im Alltag sowie dem Beitrag zur Entwicklung ihrer Handlungsfähigkeit. Die Hauptergebnisse dieser Arbeit liegen in der Konzeption von Datenbewusstsein sowie im entwickelten didaktischen Ansatz zum Lernen von Erklärmodellen im Informatikunterricht. Danach lernen Schüler:innen im Unterricht ein Erklärmodell für Datenbewusstsein und wenden es auf alltägliche Beispiele für datengetriebene digitale Artefakte an. Die empirischen Ergebnisse werden zeigen, dass Schüler:innen das Erklärmodell verstehen, sie darin eine subjektive Bedeutsamkeit für ihren Alltag erkennen und es ihre Handlungsfähigkeit in alltäglichen Situationen mit datengetriebenen digitalen Artefakten fördern kann.

ZERSTÖRUNGSFREIE ULTRASCHALLPRÜFUNG VON ORGANOBLECHEN - Moritzer, Elmar; Brandes, Philipp; Westphal, Max Siegfried; Claes, Leander; Wippermann, Mareen; Düchting, Julia; Henning, Bernd (WAK Jahresmagazin)
Keywords: Faser-Kunststoff-Verbunde (FKV); Faserverstärkte Kunststoffe (FVK); Organobleche; Ultraschall

Poisson bivectors on infinite dimensional manifolds - Michor, P. W.; Rahangdale, Praful
We show that, on a smoothly paracompact convenient manifold $M$ modeled on a convenient space with the bornological approximation property, the dual map of a Poisson bracket factors as a smooth section of the vector bundle $L_{skew}^2(T^*M,\mathbb R)$.

The Role or Rule of the Development Methodology for Additive Manufacturing - Magerkohl, Sebastian; Magyar, Balázs (Innovative Produktentwicklung durch additive Fertigung)

Europa der Kommunen - Marchetti, Andreas (Jahrbuch der Europäischen Integration 2025)

Kommunikation mit Familien im Kontext von Inklusion. Grundlagen der Zusammenarbeit mit Eltern von Kindern mit Behinderung - Albers, Timm; Meusel, Sarah (KIWI-Journal)

Towards design principles for learning environments based on theorem provers - Garnelo Abellanas, Irene (Proceedings of the Fourteenth Congress of the European Society for Research in Mathematics Education (CERME14))

CQD-SHAP: Explainable Complex Query Answering via Shapley Values

Ein Designprinzip für Lernumgebungen zu inter-aktiven Theorembeweisern - Garnelo Abellanas, Irene (Beiträge zum Mathematikunterricht 2025)

Bridging the Reality-Virtuality Gap: Evaluating Attention Markers in a Cross-Reality Application for Improved User Coordination - Yigitbas, Enes; Kröker, Leon (Proceedings of the 17th International Conference on Ubiquitous Computing and Ambient Intelligence (UCAmI 2025))

Gamification and Physiological Feedback: A Novel Approach to Reducing Glossophobia in Virtual Reality Environments - Yigitbas, Enes; Agha, Ali Amin (Proceedings of the 17th International Conference on Ubiquitous Computing and Ambient Intelligence (UCAmI 2025))

Best Practices For Empirical Meta-Algorithmic Research: Guidelines from the COSEAL Research Network - Eimer, Theresa; Schäpermeier, Lennart; Biedenkapp, André; Tornede, Alexander; Kotthoff, Lars; Leyman, Pieter; Feurer, Matthias; Eggensperger, Katharina; Maile, Kaitlin; Tornede, Tanja; Kozak, Anna; Xue, Ke; et al.

Toward Static Analysis of Immersive Attacks - Karakaya, Kadiray; Klauke, Jonas; Yigitbas, Enes (Proceedings of the 3rd International Workshop on Virtual and Augmented Reality Software Engineering (VARSE) @ ASE 2025)

A VR End-User Development Toolbox for Media Study Students - An Initial Experience Report - Krois, Sebastian; Scharke, Kevin; Yigitbas, Enes; Oevel, Gudrun (10th International Symposium on End-User Development (IS-EUD 2025))

Fachsensible wissenschaftliche Begleitung - Sloane, Hannah Sabrina; Heidebrecht, Jana; Jenert, Tobias (Prototyp Zukunft: Lösungen für transformative Lehre im Modus des Scholarship)

Feynman-Kac formula for fiber Hamiltonians in the relativistic Nelson model in two spatial dimensions - Hinrichs, Benjamin; Matte, Oliver (Proceedings of the 2023 RIMS Workshop 'Mathematical Aspects of Quantum Fields and Related Topics')
In this proceeding we consider a translation invariant Nelson type model in two spatial dimensions modeling a scalar relativistic particle in interaction with a massive radiation field. As is well-known, the corresponding Hamiltonian can be defined with the help of an energy renormalization. First, we review a Feynman-Kac formula for the semigroup generated by this Hamiltonian proven by the authors in a recent preprint (where several matter particles and exterior potentials are treated as well). After that, we employ a few technical key relations and estimates obtained in our preprint to present an otherwise self-contained derivation of new Feynman-Kac formulas for the fiber Hamiltonians attached to fixed total momenta of the translation invariant system. We conclude by inferring an alternative derivation of the Feynman-Kac formula for the full translation invariant Hamiltonian.

On the Ising Phase Transition in the Infrared-Divergent Spin Boson Model - Betz, Volker; Hinrichs, Benjamin; Kraft, Mino Nicola; Polzer, Steffen (arXiv:2501.19362)
We prove absence of ground states in the infrared-divergent spin boson model at large coupling. Our key argument reduces the proof to verifying long range order in the dual one-dimensional continuum Ising model, i.e., to showing that the respective two point function is lower bounded by a strictly positive constant. We can then use known results from percolation theory to establish long range order at large coupling. Combined with the known existence of ground states at small coupling, our result proves that the spin boson model undergoes a phase transition with respect to the coupling strength. We also present an expansion for the vacuum overlap of the spin boson ground state in terms of the Ising $n$-point functions, which implies that the phase transition is unique, i.e., that there is a critical coupling constant below which a ground state exists and above which none can exist.